2001
DOI: 10.1121/1.1365115
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electrode configuration and duration of deafness on threshold and selectivity of responses to intracochlear electrical stimulation

Abstract: This report examines the effects of intracochlear electrode configuration and mode of stimulation (bipolar or monopolar) on neural threshold and spatial selectivity in the inferior colliculus (IC) of the cat. Single and multiunit IC recordings were made in three groups of animals; acutely deafened adults (controls), neonatally deafened animals studied at 6 to 18 months of age and neonatally deafened cats studied at 2.5 to 6.5 years. Response thresholds were plotted versus IC depth to measure the spatial distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 54 publications
0
34
1
Order By: Relevance
“…It is possible that auditory deprivation may affect auditory acuity post-co-chlear implantation. Leake et al investigated this possibility using cats that were deafened for different lengths of time and then given cochlear implants [46,47]. They found that spatial selectivity of electrode impulses in the inferior colliculus was affected by the length of deafness and the amount of degeneration of the spiral ganglion cells.…”
Section: Consequences Of Early Auditory Deprivation On Development Ofmentioning
confidence: 99%
“…It is possible that auditory deprivation may affect auditory acuity post-co-chlear implantation. Leake et al investigated this possibility using cats that were deafened for different lengths of time and then given cochlear implants [46,47]. They found that spatial selectivity of electrode impulses in the inferior colliculus was affected by the length of deafness and the amount of degeneration of the spiral ganglion cells.…”
Section: Consequences Of Early Auditory Deprivation On Development Ofmentioning
confidence: 99%
“…These patients often describe perceptual distortions that may be the result of channel interaction, an inability to discriminate electrode channels or a very limited useful dynamic range for some or all channels. Previous animal experiments using model cochlear implant devices have shown that the design of the implanted electrode array and its location in the scala tympani directly affect these limitations (Shepherd et al, 1993;Xu et al, 1993;Rebscher et al, 2001). Specifically, the location of the stimulation sites on the insulating carrier, the configuration of these sites (radial, longitudinal or diagonal geometries) and the mode of stimulation used (monopolar or bipolar) measurably affected threshold, dynamic range and specificity of responses to electrical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments have included systematic evaluation of the effects of stimulating contact configurations (Rebscher et al, 2001;Snyder et al, 2004), the long-term effects of intracochlear stimulation on the survival of peripheral neurons and central nervous system reorganization (Snyder et al, 1990;Leake et al, 2000;Moore et al, 2002;Snyder et al, 2004), the temporal response characteristics of IC and cortical neurons to acute and chronic electrical stimulation Snyder et al, 1995;Schreiner and Raggio, 1996;Vollmer et al, 1999;, the effects of chronically administered neurotrophins on the peripheral and central nervous system and studies documenting how input signals presented at different intracochlear locations inhibit, mask or excite neuronal responses. The scientific study of the interaction between multiple electrical stimuli, or between electrical and acoustic stimuli, and how these stimuli are processed in the central nervous system is in its infancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations